Evolution of procalcitonin, C‐reactive protein and fibrinogen levels in neutropenic leukaemia patients with invasive pulmonary aspergillosis or mucormycosis. Issue 6 (2nd March 2016) - Roques, Marjorie; Chretien, Marie Lorraine; Favennec, Camille; Lafon, Ingrid; Ferrant, Emmanuelle; legouge, Caroline; Plocque, Alexia; Golfier, Camille; Duvillard, Laurence; Amoureux, Lucie; Bastie, Jean Noel; Maurin‐Bernier, Lory; et al.
Summary: Unlike bacterial infections, the value of procalcitonin (PCT) in detecting fungal infections in leukaemia patients is not clear. To determine whether the monitoring of PCT coupled with C‐reactive protein (CRP) and fibrinogen (Fib) could be helpful in the management of pulmonary aspergillosis (IPA) or mucormycosis (PM), we retrospectively analysed the evolution of PCT, CRP and Fib levels in 94 leukaemia patients with proven/probable IPA ( n  = 77) or PM ( n  = 17) from D−12 to D12 relative to IFI onset defined as D0. Overall, 2140 assays were performed. From D−12 to D0, 12%, 5% and 1.4% of patients had PCT >0.5, 1 and 1.5 μg l −1, respectively, while CRP was >50, 75 and 100 mg l −1 in 84%, 70% and 57% and Fib was >4, 5 and 6 g l −1 in 96%, 80% and 61% of cases respectively ( P  < 10 −7 ). The same trends were observed from D1 to D12. Overall, between D−12 and D12, only 6.4% of patients had PCT >1.5 μg l −1, while CRP >100 mg l −1 and Fib >6 g l −1 were observed in 80% and 75% of cases respectively ( P  < 10 −7 ). In leukaemia patients, IPA or PM was accompanied by a significant increase in CRP and Fib while PCT remained low.